1997
DOI: 10.1063/1.119250
|View full text |Cite
|
Sign up to set email alerts
|

Reduction mechanism of surface oxide in aluminum alloy powders containing magnesium studied by x-ray photoelectron spectroscopy using synchrotron radiation

Abstract: We investigated the reduction mechanism of surface oxide on aluminum alloy powders containing magnesium, by x-ray photoelectron spectroscopy using synchrotron radiation (SR-XPS). The reduction is the initial reaction in a new aluminum nitridation method developed by one of the authors. In heating the powders to 823 K, magnesium soluted in the powders moves from the inner region to the surface at temperatures below 573 K, and finally, above 773 K, the magnesium reduces the aluminum oxide of powder surfaces by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 13 publications
2
18
0
2
Order By: Relevance
“…It is well documented that effective solid-state sintering of Al powder can only be achieved after a considerable amount of the oxide film at the surface of the Al particles is disrupted either by mechanical deformation during compaction or Mg reduction during sintering [5][6][7][8][9][10]. To achieve strong metallurgical bonding during liquid-state sintering of Al powder, the oxide film at the surface of the Al particles must also be first disrupted, otherwise, the oxide film of each particle will serve as a hard shell preventing the Al inside, even in the liquid form, from establishing direct contact with fresh Al in the adjacent particles.…”
Section: Compactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that effective solid-state sintering of Al powder can only be achieved after a considerable amount of the oxide film at the surface of the Al particles is disrupted either by mechanical deformation during compaction or Mg reduction during sintering [5][6][7][8][9][10]. To achieve strong metallurgical bonding during liquid-state sintering of Al powder, the oxide film at the surface of the Al particles must also be first disrupted, otherwise, the oxide film of each particle will serve as a hard shell preventing the Al inside, even in the liquid form, from establishing direct contact with fresh Al in the adjacent particles.…”
Section: Compactionmentioning
confidence: 99%
“…Efficient rupture of the oxide film can be achieved by applying a high compaction pressure and more effectively by adding rigid ceramic particulates to the mixture [6,7]. The other is employing highly reactive elements such as Mg, either alloyed in the Al powder beforehand, or added in the powder mixture in the form of an elemental powder [5][6][7][8][9]. Mg acts as a solid reducing agent in the system because the free energies of formation of the resultant Mg oxides, MgAl 2 O 4 and MgO, are lower than that of Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As is known, each Al powder particle is enveloped by a stable Al 2 O 3 film, which must be disrupted to enable the sintering of aluminium [1]. Mg plays a key role in this process [19][20][21]. However, it has been found that Si improves the sintering of aluminium alloys under both nitrogen and argon [11].…”
Section: Discussionmentioning
confidence: 97%
“…Así pues, el principal efecto del magnesio es la reducción del óxido de aluminio superficial. Por encima de 500 ºC, incluso pequeñas cantidades de Mg reducen la alúmina [25] , promoviendo contactos entre partículas, lo que se traduce en una mejora de las propiedades [26] .…”
Section: Mejoras En El Procesado De Al Amunclassified